Enseñanzas de la COVID-19 - Mirabal Requena, Juan Carlos; Álvarez Escobar, Belkis; Simó Calzada, Marena (Mediciego, 2020)
Since the existence of a disease in the city of Wuhan (China) characterized by respiratory symptoms with rapid evolution towards critical condition and death was reported at the end of 2019,(1,2) the authors have reviewed multiple published articles in scientific journals that address the issue of COVID-19 from different angles